Model Pembelajaran PJOK melalui Aktivitas Bermain untuk Membangun Karakter Peserta Didik Sekolah Dasar di Kabupaten Pasaman - Mhd. Ashar (JURNAL STAMINA, 2018)
The fading character of elementary school students in Pasaman Regency, made ethics disguised. Students are faced with a shift in behavior, during learning. Easy to fight, and mock each other. Even though the nature of learning improves attitudes and behavior, it is no longer for the present. This study aims to observe PJOK learning through playing activities in elementary school. It is necessary to improve the learning method to instill the character of one of the answers to the age development in terms of education. Specific research objectives, measure the level of validity, practicality, and effectiveness of the PJOK learning model to build character. The research method used is Research and Development (R & D), research procedures Analysis, Design, Development, Implementation, Evaluation (ADDIE). Samples of 60 class V students from three schools using probability sampling techniques. Preliminary study data was collected using questionnaires, analyzed using descriptive statistics. The preliminary data of the average test scores of all sample students were 63 with five groups of test material, playing at school time 60, out of school 69, participation before playing 76, characters built 54 and constraints faced when playing 77. Data values were categorized very low, so the PJOK learning model needs to be through playing activities to build character.